Analisis Pencatatan Keuangan dan Fluktuasi Kurs terhadap Keberlanjutan Usaha UMKM Labelle Garden - Stella Stella; Immanuel Zai (Penerbit Goodwood, 2026)
Purpose: This study aims to improve financial record-keeping practices at Labelle Garden MSME and analyze the impact of rupiah–yuan exchange rate fluctuations on imported raw material costs to support business sustainability. Methodology/approach: A qualitative descriptive approach was employed using interviews, direct observation, and hands-on assistance. Financial records were developed using Microsoft Excel, supported by exchange rate analysis and simple digital rebranding through Instagram. Results: The implementation of an Excel-based financial recording system improved the accuracy and structure of financial management. Increased awareness of exchange rate fluctuations enabled better cost control, and simple rebranding enhanced the business’s visual identity and marketing effectiveness. Conclusions: Integrated financial record-keeping, exchange rate awareness, and basic rebranding contribute positively to the managerial decision-making and operational sustainability of MSME. Limitations: The implementation of simple financial recording and rebranding effectively supports MSME decision-making and marketing activities. Contributions: This study provides practical insights for MSMEs in managing financial records and mitigating exchange rate risks while strengthening their market presence, particularly for businesses relying on imported raw materials.